O sermão e seu locutor : análise lingüística e reflexões sobre o labor homilético - Samuelsson, Jeferson Andre (2008)
This dissertation is about the sermon and its preacher, concerning the writing of the sermon and its delivery. Most pastors write a sermon every week. This is a very important work that requires a lot of study, meditation, preparation and oral delivery. Therefore this dissertation is divided in three parts. The first chapter addresses the sermon and what is implied in its construction. There is a reflection about Homiletics as the area of Theology that is connected with the proclamation of God‟s word. We present the contributions of some homiletics scholars and pastors that investigated the subject with a deep love for their flock. The second chapter is about the sermon and its linguistic aspects, that is, its features as seen from a linguistic viewpoint in terms of text, speaker and language. Finally, the third chapter describes the methodology utilized and the analysis of the sermons.